Gastric Neuroendocrine Tumor and Duodenal Gastrinoma With Chronic Autoimmune Atrophic Gastritis. Issue 1 (January 2019) - Chen, William C.; Warner, Richard R. P.; Harpaz, Noam; Zhu, Hongfa; Roayaie, Sasan; Kim, Michelle Kang
Abstract : Abstract: Our group observed the first case of synchronous gastric neuroendocrine tumor (NET) and duodenal gastrinoma with autoimmune chronic atrophic gastritis (CAG), in the absence of Helicobacter pylori infection. Demographic, clinical, endoscopic, and pathologic data were abstracted from the electronic medical record at Mount Sinai Hospital from 2013 to 2015. The patient's anonymity was carefully protected, and informed consent was obtained for publication of protected health information. A 53-year-old woman with hypertension presented to Mount Sinai Hospital in June 2013 for a second opinion for management of gastric and duodenal NETs. After evaluation by gastroenterology and surgery, repeat upper endoscopy with ultrasound and fine-needle aspiration revealed multiple diminutive type I gastric NETs and 2 duodenal NETs, against a background of autoimmune CAG, with biopsy pathology negative for H. pylori . She subsequently underwent a transduodenal resection of the duodenal NETs, confirming low-grade, gastrin-positive, stage T2 duodenal NET. On routine follow-up over the next 2 years, clinical, radiographic, and endoscopic surveillance revealed no recurrent or metastatic gastric or duodenal disease. This first report of synchronous duodenal gastrinoma and gastric NET in the setting of autoimmune CAG can broaden our understanding of gastric NET pathophysiology.